Study the effect of purified alginate from Pseudomonas aeruginosa on Hep G2 and A549 cell lines. - Mohammed S. Ismaieel1 , Muthanna Hamid Hassan2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Alginate was extracted from highest alginate producer of P. aeruginosa 29 isolate, it was determined bybiochemical method (Carbazole-borate assay) and molecular method (PCR), where the amplified algD genesamples showed that clear bands at one level for all the produced isolates and molecular weight were 313 onthe leader scale. partially purified of alginate using gel filtration chromatography (Sephadex G-200) showedthe present of single peak and initial alginate fraction at 17 to last fraction 28 of alginate concentration ,where the highest alginate concentration was at fraction 23 . The cytotoxic effect of different concentrationsof purified alginate on cancer cells (HePG2 , A549 ) and normal cells WRL68 was tested. The result ofhalf-maximal inhibition concentration (IC 50) values of purified alginate treated WRL68 and HepG2 cellsafter 24,48,72 hours of incubation at 37º C were ( 187.8 , 62.0, 83.07) ?g /ml , (102.3, 42.5, 61.03) ?g/mlas respectively. While, the IC50 of purified alginate treated WRL68 and A549 cells after 24,48,72 hours ofincubation at 37ºC were ( 126.2, 63.57, 90.31 ) ?g /ml , (117.8, 57.06, 65.7) ?g /ml as respectively.